2011
DOI: 10.1007/s00296-011-1852-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinase-3 (MMP-3) and magnetic resonance imaging of sacroiliitis in assessing disease activity in ankylosing spondylitis

Abstract: The objective of this study is to evaluate the role of MMP-3 and MRI in assessing disease activity in sacroiliac joints of AS patients in comparison to the conventional measures Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Serum MMP-3 was measured in 30 patients who fulfilled the modified New York criteria for AS and in ten healthy volunteers. AS patients were categorized into those having high or low MMP-3 according to a cut-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The correlation between serological MMP3 levels and mSASSS, indicative of the role of metalloproteinases in the bone formation process, was an interesting finding and in accordance with data outlined by Maksymowych et al (47) who reported that independently of other indices, serum MMP3 levels were able to predict two-year radiographic progression in the 97 axSpA patients studied. Our data also showed that MMP3 is correlated with inflammatory markers (hs-CRP and ESR) and, in agreement with previous studies, it is increased in the serum of patients with active axSpA (24,26,27,47). The correlations between mSASS values and serum biomarkers require further evaluation by prospective studies.…”
Section: Original Papersupporting
confidence: 79%
See 2 more Smart Citations
“…The correlation between serological MMP3 levels and mSASSS, indicative of the role of metalloproteinases in the bone formation process, was an interesting finding and in accordance with data outlined by Maksymowych et al (47) who reported that independently of other indices, serum MMP3 levels were able to predict two-year radiographic progression in the 97 axSpA patients studied. Our data also showed that MMP3 is correlated with inflammatory markers (hs-CRP and ESR) and, in agreement with previous studies, it is increased in the serum of patients with active axSpA (24,26,27,47). The correlations between mSASS values and serum biomarkers require further evaluation by prospective studies.…”
Section: Original Papersupporting
confidence: 79%
“…Recent studies have focused on the role of other biomarkers to diagnose early-stage axSpA, to evaluate DA, and to predict patients at higher risk of worse outcome (16,17). Among these, matrix metalloproteinase (MMP) markers (and, in particular, MMP3) have also been considered possible biomarkers of DA given the correlation between MMP3 and CRP, DA and functional indices, such as BAS-DAI and Bath Ankylosing Spondylitis Functional Index (BASFI) (17,(24)(25)(26), and of the radiographic progression in AS patients (27). Although serum MMP3 represents a reliable parameter of DA, there is often no correlation with inflammatory MRI findings (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional studies were removed after further assessment. Finally, 13 case-control studies were analyzed in the current meta-analysis (Yang et al, 2004b;Chen et al, 2006;de Seny et al, 2008;Lin et al, 2008;Sun and Yang, 2008;Wendling et al, 2008;Wang et al, 2010;Shen et al, 2011;Ma and Yang, 2012;Soliman et al, 2012;Dhir et al, 2013;Sha and Lei, 2013;Hou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, other related documents indicated no correlation between serum MMP-3 levels and AS pathogenesis (Lin et al, 2008;Soliman et al, 2012). Therefore, the present meta-analysis aggregated previous findings from relevant studies in an attempt to systematically assess the relationship between serum MMP-3 levels and the etiology of AS.…”
Section: Introductionmentioning
confidence: 95%